Effects of different grassland use patterns on soil bacterial communities in the karst desertification areas - Chi, Yongkuan; Song, Shuzhen; Xiong, Kangning (Frontiers in Microbiology, 2023)
Soil bacteria are closely related to soil environmental factors, and their community structure is an important indicator of ecosystem health and sustainability. A large number of artificial grasslands have been established to control rocky desertification in the karst areas of southern China, but the influence of different use patterns on the soil bacterial community in artificial grasslands is not clear.In this study, three grassland use patterns (i.e., grazing (GG), mowing (MG) and enclosure (EG))were used to investigate the effects of different use patterns on the soil bacterial community in artificial grassland by using 16S rDNA Illumina sequencing and 12 soil environmental indicators. It was found that, compared with EG, GG significantly changed soil pH and increased alkaline hydrolyzable nitrogen (AN) content (P<0.05), but decreased soil total phosphorus (TP) content (P<0.05). However, MG significantly decreased the contents of soil organic carbon (SOC), total phosphorus (TP), available nitrogen (AN), ammonium nitrogen (NH4 + -N), β-1,4-glucosidase (BG) and N-acetyl-β-D-glucamosonidase (NAG) (P<0.05). The relative abundance of chemoheterotrophy was significantly decreased by GG and MG (P<0.05). GG significantly increased the relative abundance of Acidobacteria and Gemmatimonadota (P<0.05), and significantly decreased the relative abundance of Proteobacteria (P<0.05), but the richness index (Chao 1) and diversity index (Shannon) of the bacterial community in GG, MG, EG were not significantly different (P> 0.05). The pH (R 2 =0.79, P=0.029) was the main factor affecting the bacterial community structure. This finding can provide a scientific reference for ecological restoration and sustainable utilization of grasslands in the karst desertification areas.Soil microorganisms, as the engine of the biogeochemical cycle, play a central role in regulating soil fertility, plant growth and climate change (